Effect of Zn doping on the magneto-caloric effect and critical constants of Mott insulator MnV2O4 - Prashant Shahi; Harishchandra Singh; A. Kumar; K. K. Shukla; A. K. Ghosh; A. K. Yadav; A. K. Nigam; Sandip Chatterjee (AIP Advances, 2014)
X-ray absorption near edge spectra (XANES) and magnetization of Zn doped MnV2O4 have been measured and from the magnetic measurement the critical exponents and magnetocaloric effect have been estimated. The XANES study indicates that Zn doping does not change the valence states in Mn and V. It has been shown that the obtained values of critical exponents β, γ and δ do not belong to universal class and the values are in between the 3D Heisenberg model and the mean field interaction model. The magnetization data follow the scaling equation and collapse into two branches indicating that the calculated critical exponents and critical temperature are unambiguous and intrinsic to the system. All the samples show large magneto-caloric effect. The second peak in magneto-caloric curve of Mn0.95Zn0.05V2O4 is due to the strong coupling between orbital and spin degrees of freedom. But 10% Zn doping reduces the residual spins on the V-V pairs resulting the decrease of coupling between orbital and spin degrees of freedom.